2018
DOI: 10.1021/acs.jpclett.7b03229
|View full text |Cite
|
Sign up to set email alerts
|

Jahn–Teller Effect on Framework Flexibility of Hybrid Organic–Inorganic Perovskites

Abstract: Here we study the Jahn-Teller (JT) effect on framework flexibility of two analogous hybrid organic-inorganic perovskites, [C(NH)][Zn(HCOO)] (1-Zn) and [C(NH)][Cu(HCOO)] (2-Cu). Single-crystal nanoindentation measurements show that the elastic moduli and hardnesses of 1-Zn are up to ∼52.0% and ∼25.0% greater than those of the JT active 2-Cu. Temperature-dependent X-ray diffraction measurements indicate that the thermal expansion along the b-axis is switched from negative to positive by replacing Zn with Cu on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 27 publications
(35 reference statements)
2
34
0
Order By: Relevance
“…60 In other studies, the framework flexibility of [C(NH 2 ) 3 ][Cu(HCOO) 3 ] has also been shown to be increased compared to its analogous zinc formate compound due to the presence of the Jahn-Teller distortion. 61 We note that as we observe the reduction in the JT distortion under pressure, multiferroic coupling arising from JT 39 would be expected to decrease upon compression or upon chemical substitutions that reduce the volume of the equivalent unit cell.…”
Section: Discussionmentioning
confidence: 55%
“…60 In other studies, the framework flexibility of [C(NH 2 ) 3 ][Cu(HCOO) 3 ] has also been shown to be increased compared to its analogous zinc formate compound due to the presence of the Jahn-Teller distortion. 61 We note that as we observe the reduction in the JT distortion under pressure, multiferroic coupling arising from JT 39 would be expected to decrease upon compression or upon chemical substitutions that reduce the volume of the equivalent unit cell.…”
Section: Discussionmentioning
confidence: 55%
“…Up to now, the electronic and elastic properties of inorganic and organic-inorganic perovskite materials have been comprehensively researched. [17][18][19][20][21][22] However, very limited information is known about the electronic structures and elastic properties of metal-free perovskite materials, 23,24 which will certainly delay their future industrialization. In this work, the electronic and elastic properties of a family of metal-free perovskites: [(C 4 N 2 H 12 )(NH 4 X 3 )ÁH 2 O] (X = Br, Cl, I), called PIP-Cl, PIP-Br and PIP-I, respectively, have been systematically investigated, using the first principle calculations.…”
Section: Introductionmentioning
confidence: 99%
“…The crystal structure of a perovskite can be described with the chemical formula ABX 3 , in which A-sites are the organic ammonium cations, B-sites are the inorganic metal cations, and X-sites are the halide anions. The B-site cation is six-coordinated by the X-site anion to form [BX 6 ] octahedrons, which are corner-sharing to constitute three-dimensional frameworks [4,5]. These compounds have multiple quantum well structures with alternating organic and inorganic layers [6].…”
Section: Introductionmentioning
confidence: 99%